Dermatological Publications from Nepalese Dermatologist Before and During the COVID-19 Pandemic Period: A Review - Niraj Parajuli; Badri Chapagai; Sushil Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The COVID-19 pandemic created a nation-wide lockdown with hospital services resorting only to the emergency sections. Dermatology out-patient was closed with majority of services being deferred for a later date or through online platform. Here, we try to find whether Nepalese dermatologists were contributing to sciences through research.